2018
DOI: 10.1038/nature25503
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive performance is linked to group size and affects fitness in Australian magpies

Abstract: The Social Intelligence Hypothesis argues that the demands of social life drive cognitive evolution1–3. This idea receives support from comparative studies linking variation in group size or mating systems with cognitive and neuroanatomical differences across species3–7, but findings are contradictory and contentious8–10. To understand the cognitive consequences of sociality it is also important to investigate social variation within species. Here we show that in wild, cooperatively breeding Australian magpies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
398
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 237 publications
(446 citation statements)
references
References 42 publications
(65 reference statements)
17
398
5
Order By: Relevance
“…Humphrey suggested instead that the complex social dynamics experienced when such animals live in a group become the main selective force driving the evolution of primate intelligence. On page 364, Ashton et al 2 offer support for Humphrey's social-intelligence hypothesis, in a study of wild Australian magpies (Cracticus tibicen dorsalis, also known as…”
Section: A N D R E W W H I T E Nmentioning
confidence: 98%
See 4 more Smart Citations
“…Humphrey suggested instead that the complex social dynamics experienced when such animals live in a group become the main selective force driving the evolution of primate intelligence. On page 364, Ashton et al 2 offer support for Humphrey's social-intelligence hypothesis, in a study of wild Australian magpies (Cracticus tibicen dorsalis, also known as…”
Section: A N D R E W W H I T E Nmentioning
confidence: 98%
“…Social cognition has numerous other manifestations 11,12 . Yet, what Ashton et al 2 tested was essentially non-social cognition. What now begs to be fleshed out is the nature of both the social and non-social intelligence skills that may have been at work in the phenomena these authors observed.…”
Section: Brainpower Boost For Birds In Large Groupsmentioning
confidence: 99%
See 3 more Smart Citations